Pengembangan Video Praktik Yoga Untuk Meningkatkan Kualitas Hidup Usia Lanjut Di Wilayah Puskesmas Sunyaragi Kota Cirebon - Nurasih, Nurasih; Nurrochmi, Endang (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Growing old is a natural process that cannot be avoided and is a natural thing that everyone will experience. Yoga exercise is one of the exercises that is currently popular with everyone, including the elderly (elderly), because it has many benefits both for the body, soul and mind. The aim of this research is to examine the development of yoga practice videos and how they affect the quality of life of the elderly in the Sunyaragi Community Health Center area, Cirebon City. This research method is development research to test the effectiveness and efficiency of existing products in the form of elderly yoga videos. The population includes all elderly people in the Sunyaragi Community Health Center area. Elderly yoga exercises are carried out once a week for four weeks for respondents who meet the criteria. Quality of life was measured using a questionnaireWHOQOL and measurements were taken before and after yoga exercises. The data is then analyzed using testsPaired T-test. The results of statistical tests show a value of p = 0.001. The results of analysis and input from experts show that yoga videos for the elderly are safe to use as a medium for maintaining the health of the elderly. So it can be concluded that there is an influence of yoga on the quality of life of the elderly. The recommendation based on the results of this research is that yoga exercise can be used as an alternative effort to maintain health in elderly service programs at Community Health Centers.